Preservation Of Local Wisdom Of Kalinong Musical Instruments By Malay Traditional Institutions (Study In Rantau Panjang, Tabir District, Merangin Regency) - Harpin Syah; Adriansyah Adriansyah (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2022)
The goal of this research was to determine the Tabir Malay Traditional Institute's efforts to preserve the Kalinong Musical Instrument in Rantau Panjang, Tabir District, Merangin Regency. And to learn about the Tabir Malay Traditional Institute's challenges in preserving Kalinong Musical Instruments in Rantau Panjang, Tabir District, Merangin Regency. The study takes place in Tabir District, Merangin Regency. The researchers chose this location because they noticed a cultural work in the form of kalinong music that is fading in the Rantau Panjang area, Tabir sub-district, Merangin Regency. This study was conducted from January to March of 2021. The findings revealed that the Tabir Malay Traditional Institute's efforts to preserve Kalinong Musical Instruments in Rantau Panjang, Tabir District, and Merangin Regency, among others, were registered as intangible cultural heritage by the Republic of Indonesia's Ministry of Education and Culture. The certificate was presented to Jambi Province on January 6, 2017 at the Ratu Convention Center in Jambi. Furthermore, kalinong is used as music in planting events to entertain farmers who want to farm (umo) and harvest rice, and kalinong is used to welcome officials/guests. Among the challenges faced by the Tabir Malay Traditional Institute in preserving Kalinong Musical Instruments in Rantau Panjang, Tabir District, and Merangin Regency are a lack of younger generation involvement in preserving kalinong music and a lack of kalinong music players.